The United States detention system for migrants: Patterns of negligence and inconsistency - David Tellez; Lauren Tejkl; Dana McLaughlin; Maryada Vallet; Orit Abrahim; Paul B Spiegel (Elsevier, 2022)
The United States of America (US) detains more migrants than any other nation. Customs and Border Patrol (CBP) and Immigration and Customs Enforcement (ICE) detain adults and families under the Department of Homeland Security, while unaccompanied minors are housed under the Office of Refugee Resettlement (ORR) within the Department of Health and Human Services. Migrants are subject to the standards and oversight of each individual agency and facility where they are detained. This paper presents an analysis of whether the current US migrant detention system upholds the standards of each agency to maintain the health of migrants. A review of peer and grey literature, along with interviews with key informants (KI) who had worked in or visited ICE, CBP, or ORR facilities since January 2018 were undertaken. Analysis of the literature review and KI interviews covered five thematic areas: health, protection of vulnerable populations, shelter, food and nutrition, and hygiene. Thirty-nine peer-reviewed publications and 28 US Office of Inspector General reports from 2010 to 2020 were reviewed. Seventeen KI interviews were conducted. Though all three detention agencies had significant areas of concern, CBP's inability to abide by its health standards was particularly alarming. The persistence of low compliance with standards stemmed from weak accountability mechanisms, minimal transparency, and inadequate capacity to provide essential services. We have five recommendations: (1) expand independent monitoring and evaluation mechanisms; (2) standardize health standards across the three agencies; (3) develop a systematic evaluation tool to help external visitors, including members of Congress, assess the degree of implementation of standards; (4) enforce consequences for private contractors who violate standards; and (5) restrict the use of waivers that allow detention facilities to circumvent compliance with standards. Ultimately, the US federal government should explore and implement alternatives to detention to maintain the health and dignity of the individuals under its care.